Assessing the Normative Power of the European Union on Tunisian Democracy: Navigating Local Challenges at Major Crossroads - JENNANA, MARWENE BEN (İstanbul Kültür Üniversitesi, 2023)
The shared history between the European Union and Tunisia is widely deemed to evoke a longstanding relation based on mutual benefit as well as common cultural heritage. The country is considered an important historical ally of the European Union in terms of economic and military collaboration. The bilateral relations have been positively assessed until the occurrence of the arab spring in the wake of the year 2010, the period during which a third element emerged as an additional incentive for more strategic approximation. This thesis investigates the impact of the European Union (EU) on the development of democracy in Tunisia during the period from 2011 to 2022. The central research question seeks to elucidate the extent to which the EU's external aid has benefitted Tunisian democracy while shedding light on the responsiveness of the 2019 regime to the European implementation of the domestic democratic framework. To answer this question, In addition, the researcher conducted interviews with diplomats and state personnel from Tunisia who have vested work and time in both the pre-revolution and post-revolution periods. The study contends that the EU sought to bring a modernizing parameter to Tunisia by providing financial, political, and technical aid that sought to install solid democracy in the country. However, the researcher found that the EU's efforts were originally insufficient and non-conforming the initial rhetoric of EU officials. The study also argues that the Tunisian democratic example has been undermined by the events of July 25, 2021, which obliged the country to regress back into one-man rule primarily spearheaded by the freezing of the work of the national assembly due to corruption and economic issues that preceded it caused mainly by the COVID-19 pandemic
Avrupa Bı̇rlı̇ğı̇'nı̇n Tunus Demokrası̇sı̇ Üzerı̇ndekı̇ Normatı̇f Gücünün Değerlendı̇rı̇lmesı̇: Büyük Kavşak Noktasında Yerel Güçlüklerı̇n Üstesı̇nden Gelmek
▪ Yüksek lisans tezi.
Keywords: Tunisian exceptionalism; Democracy; Normative Power; EU foreign policy; Arab Spring